Mass spectrometry evidence for self-rigidification of π-conjugated oligomers containing 3, 4-ethylenedioxythiophene groups using RRKM theory and internal energy calibration. Issue 2 (April 2019) - Rondeau, David; Gimbert, Yves; Vékey, Károly; Dráhos, Laszlo; Turbiez, Mathieu; Frère, Pierre; Roncali, Jean
The self-rigidification of ionized π-conjugated systems based on two combinations of thiophene (T) and 3, 4-Ethylenedioxythiophene (E) is investigated using mass-analyzed ion kinetic energy spectrometry (MIKES) of ions produced from electron impact ionization at 70 eV. The m/z 446 radical cations of the two isomers ETTE and TEET lead to detect m/z 418 and 390 daughter ions. The MIKE spectra differ only by the intensities of these fragment ions. As the m/z 418 daughter ion is produced through a same retro-Diels Alder reaction whatever the fragmenting isomer, the difference in daughter ion intensities is interpreted in term of unimolecular dissociation rate constants ( k ( E int )) ratios. Considering that the transition state (TS) of such reaction is attributed to a quinoid form, equivalent vibration modes are assumed for the TS of both dissociating ETTE and TEET radical cations. As a result, by using the Rice–Ramsperger–Kassel–Marcus (RRKM) theory, the difference in daughter ion intensities is interpreted by considering that the fragmenting ion is more or less ordered in its ground state than at the transition state, resulting from the influence of the number of the S … O interactions in the planarization of the TEET ion toward the ETTE charged species. The comparison of this behavior in MIKES experiments is supported by the modeling of ion behavior in mass spectrometer and the calibration in internal energy of the radical cations produced in an EI source.